2015
DOI: 10.1007/s00464-015-4459-4
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of a novel pain management strategy: evaluating the impact on patient outcomes

Abstract: Our multimodal pain management strategy reduced intraoperative opioid administration. Postoperatively, improvements in PACU time, postoperative pain and narcotic use, and lengths of stay were seen in the experimental cohort. With the favorable finding from the pilot study, further investigation is warranted to fully evaluate the impact of this pain management protocol on patient satisfaction, clinical and financial outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 39 publications
2
36
0
Order By: Relevance
“…Studies of multimodal pain management in other postsurgical environments including liver resection have demonstrated patterns of similar or shortened recovery times and hospital lengths of stay relative to non‐MPM strategies . We unexpectedly found that patients in the post‐MPM group recovering from liver transplantation experienced longer hospitalizations as well as more time spent in the ICU relative to patients in the pre‐MPM group.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Studies of multimodal pain management in other postsurgical environments including liver resection have demonstrated patterns of similar or shortened recovery times and hospital lengths of stay relative to non‐MPM strategies . We unexpectedly found that patients in the post‐MPM group recovering from liver transplantation experienced longer hospitalizations as well as more time spent in the ICU relative to patients in the pre‐MPM group.…”
Section: Discussionmentioning
confidence: 68%
“…Studies of multimodal pain management in other postsurgical environments including liver resection have demonstrated patterns of similar or shortened recovery times and hospital lengths of stay relative to non-MPM strategies. 13,[25][26][27] We unexpectedly found that patients in the post-MPM group recovering from liver transplantation experienced longer hospitalizations as well as more time spent in the ICU relative to patients in the pre-MPM group. Although intraoperative transplant case duration and blood product use was similar between the groups, a trend toward a higher proportion of patients requiring reintubation and a numerically higher proportion of patients returning to the operating room in the post-MPM group was noted.…”
Section: Discussionmentioning
confidence: 99%
“… 107 A post-induction, pre-incision bilateral TAP block combined with local peritoneal infiltration at port sites with long-acting liposomal bupivacaine reduced initial and final PACU pain scores and shorten PACU times. 108 …”
Section: Regional Anesthesia Techniquesmentioning
confidence: 99%
“…A recent meta-analysis showed that novel infiltration techniques such as wound catheter, TAP block, and intraperitoneal instillation led to a decrease in pain scores (32). TAP block was rarely applied in the present cohort, but might represent an alternative to conventional wound infiltration (5,33). Another reason for insufficient pain relief by wound infiltration might be a lack of proper follow-up with consequent insufficient administration of backup pain medication.…”
Section: Discussionmentioning
confidence: 79%
“…Enhanced recovery after surgery (ERAS) pathways advocate minimally invasive surgery to decrease surgical stress, morbidity, length of stay and costs (4). ERAS care protocols including multimodal pain management strategies aim to facilitate recovery by an opioidsparing attitude to avoid opioid-related side effects (5). Epidurals have been shown to be efficient after open surgery (6), and modern pain management strategies including intravenous lidocaine, wound infiltration or transverse abdominis plane (TAP) block emerge as alternatives for minimally invasive surgery (7).…”
Section: Introductionmentioning
confidence: 99%